Antenatal diagnostic and treatment of congenital infection coused by parvovirus B19 (clinical case) - A. A. Grineva; V. V. Vasilev; T. A. Kashtanova; I. V. Kyanksep (Журнал инфектологии)
Parvovirus infection is a widespread disease with a high risk of transplacental transmission among infected pregnant women, which leads to fetal death or the development of severe congenital disease in the newborn. Modern approaches to the diagnosis and treatment of parvovirus infection in pregnant women provide the opportunity for a favorable outcome of the disease, preserving the life and health of the child. A clinical case of antenatal diagnosis and treatment of congenital parvovirus infection with the development of severe anemia in the fetus and the results of postnatal observation are presented.